2011
DOI: 10.1007/s10956-011-9311-6
|View full text |Cite
|
Sign up to set email alerts
|

How Do Pre-Service Science Teachers’ Views on Science, Scientists, and Science Teaching Change Over Time in a Science Teacher Training Program?

Abstract: Every aspect of teaching, including the instructional method, the course content, and the types of assessments, is influenced by teachers' attitudes and beliefs. Teacher education programs play an important role in the development of beliefs regarding teaching and learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 60 publications
1
18
1
5
Order By: Relevance
“…It helps to advocate local voices, local realities and local wisdom in the course of completing all the cycles. These key characteristics of PAR are in line with McNeill (2003) and Ucar (2011), argue !connection of participatory research movement with emancipatory social change at broader levels, and thereby, with goals to which all social research should aspire".…”
Section: Introductionsupporting
confidence: 77%
“…It helps to advocate local voices, local realities and local wisdom in the course of completing all the cycles. These key characteristics of PAR are in line with McNeill (2003) and Ucar (2011), argue !connection of participatory research movement with emancipatory social change at broader levels, and thereby, with goals to which all social research should aspire".…”
Section: Introductionsupporting
confidence: 77%
“…in England, She's (1995) study in Taiwan, Song and Kim's (1999) study in South Korea, Barman's (1999) study in USA, Fung's (2002) study in China, Rubin, Bar and Cohen's (2003) study in Israel, Medina-Jerez, Middleton and Orihuela-Rabaza's (2011) study in Bolivia and Columbia, Ruiz-Mallen and Escalas's (2012) study in Spain and Christidou's (2010) study in Greece reported that students at different educational levels had stereotypical scientist images. Similarly, studies in Turkey which described students' scientist images by generally using DAST, such as the studies by Muşlu and Macaroğlu-Akgül (2006), Özgelen (2012), Yontar-Toğrol (2013), Özel and Doğan (2013) and Karaçam (2015b) on primary school students, by Akçay (2011) on primary and secondary school students and by Demirbaş (2009) and Uçar (2012) on teacher candidates, found that students dominantly had stereotypical scientist images although they were at different educational levels. There are many assumptions regarding the reasons why students have scientist images that can be defined as stereotypical in the studies conducted in our country and in other countries.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 96%
“…Among these studies, Özel and Doğan (2013), Özgelen (2012), Karaçam (2015), Türkmen (2008), and Yontar-Toğrol (2013) determined the images of primary school students; Akçay (2011) investigated the images of primary and secondary school students; and Bilen et al (2012), Demirbaş (2009) and Uçar (2012), researched the images of teacher candidates. As a result of these studies, researchers stated that students predominantly have scientistimage stereotypes and that students' gender, age, academic educational department, and socio-economic level are the factors that affect their scientist-image.…”
Section: Theoretical Frameworkmentioning
confidence: 99%